Estimativas de parâmetros genéticos e fenotípicos para características de crescimento até a desmama em bovinos da raça Canchim - Mascioli, Arthur Dos Santos [UNESP]; De Paz, Cláudia Cristina Paro [UNESP]; El Faro, Lenira [UNESP]; De Alencar, Maurício Mello; Trematore, Renata Lima; De Andrade, Angelina Bossi Fraga [UNESP]; Leite Oliveira, José de Anchieta (My University, 1997)
The objective of this work was to obtain heritability and genetic, phenotypic and environmental correlations estimates for birth (BW) and weaning (WW) weights and average daily gain from birth to weaning (ADG) of Canchim (5/8 Charolais + 3/8 Zebu) calves. The data were analyzed by least squares method, with models that included the fixed effects of genetic group of sire (5/8 Charolais + 3/8 Zebu and Canchim), year and season of birth of calf, sex of calf and age of cow at calving, and the random effects of sire within genetic group. All effects included in the models affected significantly all traits studied, except year of birth that affected only BW, and season of birth that did not affect BW. The heritability estimates obtained were equal to 0.76 ± 0.18 (BW), 0.43 ± 0.15 (WW) and 0.37 ± 0.14 (ADG). The genetic correlations were 0.60 ± 0.17 (BW and WW), 0.38 ± 0.23 (BW and ADG) and 0.97 ± 0.02 (WW and ADG). The phenotypic and environmental correlations were, inthe same order, 0.36 and 0.09, 0.17 and -0.06 and 0.98 and 0.99, respectively. The results obtained suggest that selection should result in genetic progress for all traits studied, but mainly for BW. Selection for ADG should result in progress for WW with little changes in BW.
Genetic and phenotypic parameters estimates of preweaning growth traits of Canchim cattle
Keywords: Beef cattle; Canchim; Weights selection; Bos indicus; Bos taurus